Acute thoracic aortic dissection: a case report - Dewa Ayu Ratna Dewi; Made Dwija Putra Ayusta (DiscoverSys Inc., 2020)
Introduction: Aortic dissection (AD) is the most common aortic emergency, result in a catastrophic outcome. Patients usually asymptomatic, some of them present with sudden severe, tearing or sharp back or anterior chest pain and haemodynamic disturbance. Early and accurate diagnosis and treatment determine the patient outcome.Case Report: A case of 40 years old man complained of acute, sharp, chest pain since 4 days before admission which worsen instead of medical treatment, with a history of smoking since a few years ago. A vital sign was within normal limit. Laboratory result showed high CKMB, troponin T, LDH result. Occasional ventricular extrasystoles and inferior ischaemic was found in the ECG examination. From echocardiography, the patient suspected to have aortic dissection Stanford type A since an intimal flap on ascending aorta was found, with left ventricle hypertrophy, dilatation of right atrium and right ventricle, severe aortic regurgitation, moderate mitral regurgitation, severe tricuspid regurgitation, moderate pulmonary regurgitation and moderate pulmonary hypertension. From plain radiography, the patient showed mediastinum widening and cardiomegaly, CT angiography showed Stanford type A aortic dissection (DeBakey type I).Â The patient refused to seek further treatment for operation as suggested.Conclusion: It is still challenging to differentiate aortic dissection (AD) and another acute chest emergency. Since clinical presentation and laboratory result may be similar between those illnesses. Therefore careful history taking and further imaging examination should be considered to increase the patient outcome.